1991
DOI: 10.1088/0953-8984/3/43/008
|View full text |Cite
|
Sign up to set email alerts
|

Critical behaviour of the conductivity in metallic n-type InP close to the metal-insulator transition

Abstract: The metal-insulator transition (MIT) induced by a magnetic field. in barely metallic and compensated n-type InP has been re-examined. Using new analysis methods, we have determined the magnetic field for which the conductivity change from a metallic behaviour to avariable-range hoppingregime. On themetallicsideoftheMl~, the electricalmnduciivity is found to obey a = a. + mT' down to 60 mK: the zero-temperature conductivity can be described by a scaling law with an exponent U = 1 and there is no evidence for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
(4 reference statements)
1
16
0
Order By: Relevance
“…We have noted that when the magnetic field B < 9 T, the slope corresponds to 1,6 ( ( 0) L in this region. In fact, Biskupski et al [1] showed that when the MIT approached the relevant length is T L and in the critical region the electrical conductivity has a 1/ 3…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…We have noted that when the magnetic field B < 9 T, the slope corresponds to 1,6 ( ( 0) L in this region. In fact, Biskupski et al [1] showed that when the MIT approached the relevant length is T L and in the critical region the electrical conductivity has a 1/ 3…”
Section: Resultsmentioning
confidence: 82%
“…In fact, Biskupski et al [1] showed that when the MIT approached the relevant length is T L and in the critical region the electrical conductivity has a 1/ 3…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biskupski et al 1 , and El kaaouachi et al 2 have observed the metal-insulator transition (MIT) induced by a impurity concentration in barely metallic and compensated n-type InP. Using new analysis methods, they determined the critical magnetic field C B for which the conductivity changes from a metallic behaviour to a variable range hopping regime.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic field induced localization is often observed as a change from a non-activated to an activated conductivity in semiconduction which are degenerate at low temperatures at zero magnetic field [1]. In a typical experimental procedure much care is taken to maintain a sample as close to the thermodynamic equilibrium as possible.…”
Section: Introductionmentioning
confidence: 99%